MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MENCERITAKAN KEMBALI TEKS FABEL KELAS VII - Simorangkir, Odilia Veronica (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
This research aims to determine the effect of using the picture and picture learning model on the ability to retell fable texts in class VII of SMP Negeri 6 Percut Sei Tuan. In this research, the model used is a qualitative method, a research method using Quasi Experiment, and a two group posttest design research design. The subjects in this study were 64 people who were divided into two classes, namely class VII-5 as the control class group and VII-1 as the experimental class group, where each number of students was 32 people. The data collection techniques used are observation, interviews, tests and documentation. Based on the results of the test data analysis, it can be seen that the average score for the control class group is 77.37 in the good category and the experimental class group is 83.62 in the very good category. Apart from that, the normality and homogeneity tests show that the results obtained are normal and homogeneous. Through hypothesis testing, results show with tcount 4.60 and ttable 1.67, where the tcount obtained is greater than ttable, namely 4.60 > 1.67, so it can be stated that the hypothesis (Ha) is accepted. This proves that the Picture and Picture Learning Model influences the ability to retell fable texts in class VII students at SMP Negeri 6 Percut Sei Tuan for the 2023/2024 academic year.